Kompetensi Komunikasi Lintas Budaya pada Aspek Pengetahuan Siswa - Sahendra, Yani; Harlina, Harlina (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
This study aims to determine the competence of cross-cultural communication on aspects of knowledge of students at SMK Negeri 6 Palembang. A quantitative descriptive method was used. This research data use secondary data, and the data was collected by using the Likert model of cross-cultural communication competence psychological scale (Harlina, et al., 2021). The total population in this study was 262 students, the determination of the number of samples using the Slovin formula, from the calculations obtained the number of samples used as many as 158 students who were selected randomly with proportional random sampling technique. The data analysis technique uses the percentage formula with the Microsoft Office Excel 2016 program. The results showed that the cross-cultural communication competence in the knowledge aspects is very high category 22 students (14%), high category 39 students (25%), medium category 28 students (18%), low category 65 students (41%), very low category 4 students (3%). Based on the data above, it can beconcluded that all respondents at SMK Negeri 6 Palembang show that the competence of cross-cultural communication in the knowledge aspect is in a low category.